2013
DOI: 10.4000/books.pur.47974
|View full text |Cite
|
Sign up to set email alerts
|

Le Jari

Abstract: Extrêmement difficile d'accès pour sa plus grande partie, située aux confins de la Guyane française et du Brésil, la région du Jari a fasciné les colonisateurs et les a aimantés pendant plusieurs siècles. On y a cherché l'Eldorado, le lac Manoa ou plus prosaïquement (mais cela revient au même) de fabuleuses mines d'or. Une rude compétition entre la France et le Brésil a rendu un verdict amer pour la première, vainqueur de la bataille de la connaissance avec des explorateurs comme Jules Crevaux et Henri Coudrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…In 2015, the SHIVA trial compared molecularly targeted therapy versus conventional therapy in 741 participants with metastatic refractory solid tumours. The study reported no significant improvement in progression-free survival compared to standard (non-targeted) treatment (Le Tourneau 2015). In contrast, a recent meta-analysis of 346 phase I trials including 13,203 people found that biomarkerbased targeted therapy was associated with an improved median progression free survival (median 5.7 months versus 2.95 months) (Schwaederle 2016).…”
Section: How the Intervention Might Workmentioning
confidence: 94%
“…In 2015, the SHIVA trial compared molecularly targeted therapy versus conventional therapy in 741 participants with metastatic refractory solid tumours. The study reported no significant improvement in progression-free survival compared to standard (non-targeted) treatment (Le Tourneau 2015). In contrast, a recent meta-analysis of 346 phase I trials including 13,203 people found that biomarkerbased targeted therapy was associated with an improved median progression free survival (median 5.7 months versus 2.95 months) (Schwaederle 2016).…”
Section: How the Intervention Might Workmentioning
confidence: 94%
“…This view is supported by Roger Le Tourneau, who wrote that Ṣāliḥ may have been influenced by the Shīʿī Mahdī thought: "…the fact that Ṣāliḥ promised that he would return when the seventh chief of the Barghawāṭah had assumed power and declared that he was the Mahdī who would fight against the Antichrist (al-Dajjāl) at the coming of the end of the world with the help of Jesus, can be considered a sign of Shīʿī influence." 67 Similarly, Abdallah Laroui claims that Ṣāliḥ's prophethood was based on remains of an earlier form of Christianity, but it was a branch of Shīʿī doctrine. 68 In addition to these hypotheses and interpretations, the sociocultural and geographical situation of Ṣāliḥ's tribe, Barghawāṭah, may have also been influential in his claims about the Mahdī and prophethood.…”
Section: The Reasons For ṣāLiḥ Ibn ṭArīf's Claim Of Being Mahdīmentioning
confidence: 99%
“…Im Ausgangspunkt werden Zinsen im französischen Recht nicht wieder verzinst. 142 Gemäß Art. 1154 C.civ.…”
Section: Zinseszinsenunclassified
“…GWB-Novelle Wolfgang Wurmnest, New Era for Private Antitrust Litigation in Germany, A Critical Appraisal of the Modernized Law against Restraints of Competition: German L. J. 6 (2005) 1173-1190; Rolf Hempel, Private Follow-on-Klagen im Kartellrecht: Wirtschaft und Wettbewerb (WuW) 2005, 137-146 (142)(143)(144)(145)(146); die Entwicklungen in der EU haben zudem eine Reforminitiative in der Schweiz angestoßen, siehe Andreas Heinemann, Strukturberichterstattung Nr. 44/4, Evaluation Kartellgesetz, Die privatrechtliche Durchsetzung des Kartellrechts (2009); siehe auch allgemein Clifford A. Jones, After the Green Paper: The Third Devolution in European Competition Law and Private Enforcement: Competition L. Rev.…”
unclassified